2017
DOI: 10.17219/pzp/64695
|View full text |Cite
|
Sign up to set email alerts
|

Ways of coping with stress: Survey based on the group of students from selected universities in Lublin

Abstract: Nie występujePraca wpłynęła do Redakcji: 1.04.2016 r. Po recenzji: 13.07.2016 r. Zaakceptowano do druku: 17.08.2016 r. StreszczenieWprowadzenie. We współczesnym świecie niemalże na każdym kroku ludność jest narażona na stresujące sytuacje. Stres jest osobistym doświadczeniem, niepowtarzalną kombinacją reakcji fizjologicznych, zachowań, emocji. Naturalną reakcją na wystąpienie stresu jest dążenie do ograniczenia jego działania przez "mechanizm copingu". Zdaniem Lazarusa radzenie sobie ze stresem to podejmowanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…They emphasize the legitimacy of effective interventions counteracting educational stress, which would not only favour the development of skills, but also reduce its negative health effects. Other authors also pointed to the significant importance of support in strengthening positive self-image [ 52 , 53 ], or mobilization to fight stress [ 54 , 55 ]. In the conducted research, it was unequivocally shown that students who felt greater support from the teacher significantly more often “looked for instrumental support”.…”
Section: Discussionmentioning
confidence: 99%
“…They emphasize the legitimacy of effective interventions counteracting educational stress, which would not only favour the development of skills, but also reduce its negative health effects. Other authors also pointed to the significant importance of support in strengthening positive self-image [ 52 , 53 ], or mobilization to fight stress [ 54 , 55 ]. In the conducted research, it was unequivocally shown that students who felt greater support from the teacher significantly more often “looked for instrumental support”.…”
Section: Discussionmentioning
confidence: 99%
“…Substance use, denial, behavioral disengagement, and religious coping were used the least frequently by Polish students to cope with stress during the pandemic. Among all groups of people in education, students exhibited higher levels of emotional problems and pressure related to the changes in the educational and social situation during the pandemic than did primary and high school students [63,64]. Thus, it was important to assess their need for support and the sources they expect this support from.…”
Section: Plos Onementioning
confidence: 99%